Second language anxiety: gender influence, beliefs about language learning and second language achievement/ Tracy William Tandang - William Tandang, Tracy (2019)
English language is an important language and the use of this language has extended in formal occasions, media, jurisdiction, and even in daily conversations. Malaysians are using the language widely and the language is introduced formally to young learners as early as kindergarten years. There are many aspects and factors that should be considered in second language learning and one of the crucial aspects in second language learning is second language anxiety. Second language anxiety is believed to have a debilitating effect on the learners’ performance. This study was conducted to better help educators in Malaysia to understand the second language anxiety and beliefs about language learning among Malaysian students. Furthermore, the study also looked at second language anxiety across gender as previous research has indicated discrepancy across genders in second language learning. Thus, a quantitative research with correlational approach design was conducted by using 334 polytechnic students from Commerce Department as the samples. From the findings, it is found that the students have moderate level of anxiety and positive beliefs about language learning. Apart from that, it is also portrayed that the higher the anxiety is, the lower the achievement of the English test. Findings from this study have also indicated that there is no significant difference across gender for second language anxiety.